2014
DOI: 10.1002/app.40379
|View full text |Cite
|
Sign up to set email alerts
|

Biobased thermosetting resins composed of L‐lysine methyl ester and bismaleimide

Abstract: Lysine methyl ester (LME), which was generated in situ by the reaction of lysine methyl ester dihydrochloride and triethylamine in dimethyl sulfoxide (DMSO), was prepolymerized with 4,4′‐bismaleimidodiphenylmethane (BMI) at 80°C for 2 h in DMSO. Then, the formed prepolymer was precipitated in water. The obtained LME/BMI prepolymers with molar ratios of 2:2, 2:3, and 2:4 were compression‐molded at a final temperature of 230°C for 2 h to produce cured lysine methyl ester/4,4′‐bismaleimidodiphenylmethane resins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Li et al [34] reported a polymer network by the reaction of a cycloaliphatic epoxy resin with DL-lysine, or diglycidyl ether of bisphenol A with L-tryptophan [35]. We also reported a polymer network by the reaction of 4,4"-bismaleimidodiphenylmethane with L-lysine [36]. Recently, radical-mediated thiol-ene 'click' reactions have attracted increasing attention as a method for the production of crosslinked polymer networks with various frameworks and functional groups [37][38][39][40].…”
Section: T1 Introductionmentioning
confidence: 85%
“…Li et al [34] reported a polymer network by the reaction of a cycloaliphatic epoxy resin with DL-lysine, or diglycidyl ether of bisphenol A with L-tryptophan [35]. We also reported a polymer network by the reaction of 4,4"-bismaleimidodiphenylmethane with L-lysine [36]. Recently, radical-mediated thiol-ene 'click' reactions have attracted increasing attention as a method for the production of crosslinked polymer networks with various frameworks and functional groups [37][38][39][40].…”
Section: T1 Introductionmentioning
confidence: 85%
“…ML and DAIC can undergo MHB as is shown in Figure , in a similar manner to melamine cyanurate analogs . Amino groups of ML are possible to undergo Michael addition with maleimide groups of BMI in a similar manner to the curing reaction of BMI and DDM . Leu reported that addition copolymerization of triallyl isocyanurate and BMI occurs when triphenylphosphine (TPP) was used as a catalyst .…”
Section: Introductionmentioning
confidence: 92%
“…[24][25][26][27] Amino groups of ML are possible to undergo Michael addition with maleimide groups of BMI in a similar manner to the curing reaction of BMI and DDM. 28,29 Leu reported that addition copolymerization of triallyl isocyanurate and BMI occurs when triphenylphosphine V C 2015 Wiley Periodicals, Inc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these disadvantages and extend the application of BMI, great efforts have been made to improve the processability of BMI while maintaining its excellent thermal performance. One strategy is the copolymerization of BMI with expanding agents or other high performance resins such as diamine, allylic compound, cyanate ester, epoxy resins, and benzoxazine . Another effective strategy is the modification of BMI's chemical structure.…”
Section: Introductionmentioning
confidence: 99%